2012
DOI: 10.1155/2012/609148
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a MCF-7 Breast Cancer Cell Subpopulation with High Sensitivity to IL-1β: Characterization of and Correlation between Morphological and Molecular Changes Leading to Increased Invasiveness

Abstract: Cancer and inflammation are closely related in tumor malignancy prognosis. Breast cancer MCF-7 cells have a poor invasive phenotype, although, under IL-1β stimulus, acquire invasive features. Cell response heterogeneity has precluded precise evaluation of the malignant transition. MCF-7A3 cells were selected for high sensitivity to IL-1β stimulus, uniform expression of CXCR4, and stability of IL1-RI. Structural changes, colony formation ability, proliferation rate, chemotaxis, Matrigel invasion, E-cadherin mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Upon IL1β stimulation, breast cancer cells acquire certain features of an invasive phenotype as the loss of cell-cell contact, the acquisition of a fibroblastoid cytoarchitecture and cell scattering 14 15 36 . Nicely recapitulating the abovementioned results, medium collected from E2 and G-1 treated CAFs induced a fibroblast-like phenotype (as evaluated by the polarity index) in SkBr3 cells transfected with a shRNA and exposed to E2 and G-1, but not in SkBr3 cells transfected with a shGPER ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon IL1β stimulation, breast cancer cells acquire certain features of an invasive phenotype as the loss of cell-cell contact, the acquisition of a fibroblastoid cytoarchitecture and cell scattering 14 15 36 . Nicely recapitulating the abovementioned results, medium collected from E2 and G-1 treated CAFs induced a fibroblast-like phenotype (as evaluated by the polarity index) in SkBr3 cells transfected with a shRNA and exposed to E2 and G-1, but not in SkBr3 cells transfected with a shGPER ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…High levels of IL1β within the tumor microenvironment have been associated with increased recurrence and metastasis in breast cancer 4 9 12 13 . In this regard, it has been shown that breast cancer cells exposed to IL1β may acquire an invasive phenotype through diverse structural changes as the loss of cell-cell contact, the acquisition of a fibroblastoid cytoarchitecture and cell scattering 14 15 . Moreover, a positive correlation between IL1β levels and estrogens was found in breast tissue biopsies and the ability of estrogens to stimulate IL1β production was recently reported both in vitro and in breast cancer xenografts 10 11 .…”
mentioning
confidence: 99%
“…Human breast MCF7 cancer cells are commonly used for studying the biology and drug resistance development process of ER + (or luminal A subtype-like) breast cancer (Comşa et al, 2015). Although MCF7 was originally thought to be a monoclonal cell line, it was recently discovered as a population of breast cancer cells (mostly ER + ) with high levels of molecular heterogeneity (Leung et al, 2010;Pérez-Yépez et al, 2012;Khan et al, 2017;Roden et al, 2018). In this study, we identified a subpopulation (or a subline) of MCF7 cells (i.e., the ERα low /β low -p53 −/low -HER2 low -Smac low -XIAP hi -Bcl-2β + MCF7-TAM12.5 cells), which exhibit higher therapeutic tolerance (i.e., cell death resistance, during primary challenge) and have differential metastatic potential and clonogenic responses (upon rechallenge) against tamoxifen.…”
Section: Discussionmentioning
confidence: 99%
“…MCF-7 parental cells also maintain the expression of epithelial markers, such as E-cadherin, β-catenin and cytokeratin 18 (CK18) and other specific molecular markers of natural epithelial layers, such as claudins and zona occuldens protein 1 (ZO-1), among other proteins that constitute the intercellular junctions. Furthermore, MCF-7 are mesenchymal markers negative, these markers are including vimentin and smooth muscle actin (SMA) [ 28 , 29 ]. FROP-1 peptide was identified by phage display technology by Sabine Zitzmann research group in 2007 [ 13 ].…”
Section: Discussionmentioning
confidence: 99%